[tex]w=\frac{k}{1-n}(v^{1-n}_{2}-v^{1-n}_{1})[/tex](adsbygoogle = window.adsbygoogle || []).push({});

let [tex]k=pv^n[/tex]

[tex]\frac {p_{2}v^{n}_{2}v^{1-n}_{2} - p_{1}v^{n}_{1}v^{1-n}_{1}}{1-n}[/tex]

how can this become

[tex]w=\frac {p_{1}v_{1} - p_{2}v_{2}}{n-1}[/tex]

thanks

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Simplifying this equation

**Physics Forums | Science Articles, Homework Help, Discussion**